On the Speciation of Iodine in Marine Aerosol. Issue 4 (17th February 2022) - Gómez Martín, Juan Carlos; Saiz‐Lopez, Alfonso; Cuevas, Carlos A.; Baker, Alex R.; Fernández, Rafael P.
Abstract: We have compiled and analyzed a comprehensive data set of field observations of iodine speciation in marine aerosol. The soluble iodine content of fine aerosol (PM1 ) is dominated by soluble organic iodine (SOI; ∼50%) and iodide (∼30%), while the coarse fraction is dominated by iodate (∼50%), with nonnegligible amounts of iodide (∼20%). The SOI fraction shows an equatorial maximum and minima coinciding with the ocean "deserts, " which suggests a link between soluble iodine speciation in aerosol and ocean productivity. Among the major aerosol ions, organic anions and non‐sea‐salt sulfate show positive correlations with SOI in PM1 . Alkali cations are positively correlated to iodate and negatively correlated with SOI and iodide in coarse aerosol. These relationships suggest that under acidic conditions iodate is reduced to HOI, which reacts with organic matter to form SOI, a possible source of iodide. In less acidic sea‐salt or dust‐rich coarse aerosols, HOI oxidation to iodate and reaction with organic matter likely compete. Plain Language Summary: Iodine has a profound impact on tropospheric chemistry and plays a key role in in mammalian metabolism. Marine aerosol is an atmospheric iodine reservoir and its carrier to continental food chains. However, the chemistry behind the varying concentrations of iodine‐bearing species observed in aerosol is poorly understood, which hinders model predictions about iodine recycling to the gas phase and accumulation in aerosol. To shed some light on this problem, we have compiled and analyzed a global data set of field observations of iodine speciation in aerosol over the ocean between 1983 and 2018. Comparison of the spatial trends of the relative amounts of soluble iodine species in aerosol and ocean surface remote sensing variables reveals a link to ocean productivity, which points to an important role of organics emitted by the ocean and condensed on aerosol surfaces. Furthermore, the speciation of iodine differs between coarse and fine aerosol, which are originated, respectively, from condensation of gases derived from ocean surface emissions (sulfate aerosol) and aeolian processes (sea salt and dust) and, as a consequence of their different composition, have different pH. Overall, organic matter and acidity emerge from our study as the factors controlling iodine speciation in marine aerosol. Key Points: Iodide and SOI are more abundant in PM1, while the coarse fraction is dominated by iodate; iodide is only 30% lower in the coarse fraction Iodine speciation in fine aerosol is related to ocean productivity and present a distinct latitudinal variation Different chemical regimes correlated with acidic and alkali ions prevail in fine and coarse aerosol speciation